Assessment of Nutrition-Related Biochemical Parameters before and during he COVID-19 Pandemic - Hakan Bor; Murat Semerci (Middle Black Sea Journal of Health Science, 2026)
Objective: This study compared serum glucose and lipid levels between the pre-pandemic and pandemic periods.Methods: In this retrospective, record-based study, serum biochemical data from patients who visited a regional state hospital between February 1, 2019 and May 31, 2021 were used. The data were divided into two equal time periods: a pre-pandemic period (February 1, 2019–March 31, 2020) and a pandemic period (April 1, 2020–May 31, 2021). In addition to general comparisons between the two groups, they were also analyzed by age, sex, and seasonal categories.Results: Data from a total of 293,462 laboratory records were included in the study. Pre-pandemic and pandemic groups were compared on a general basis, independent of age, sex, and seasonal effects. During the pandemic, individuals' serum glucose, total cholesterol, low-density lipoprotein cholesterol (LDL-C), and triglyceride levels increased, while high-density lipoprotein cholesterol (HDL-C) levels decreased. Conclusion: The findings indicate that the pandemic period was associated with a less favorable serum glucose and lipid profiles compared with the pre-pandemic period (p